Diseño e implementación de un sistema para el procesamiento de imágenes satelitales NOAA empleando MATLAB - Enríquez Guerra, Lizette Estefanía (2017)
This project involves the design and implementation of a system for NOAA satellite image processing using MATLAB. For system development the first step is to connect to a NOAA satellite signal frequency modulation, the obtained signal is processed through an interface block in the Matlab software. The project uses devices such as an antenna, a radio receiver and a computer on which the program Matlab is installed. For this project the written part of four chapters distributed as follows is structured: Chapter 1: Research topics for project development are described; a brief description of satellite systems, antenna and receiving means. Chapter 2: This chapter describes the design and implementation of the system for image processing and a general framework for such processing in Matlab platform is explained. Chapter 3: This chapter describes the validation of the prototype in different scenarios of simulation and system testing operation. Chapter 4: Finally in this chapter the conclusions and recommendations obtained during the development of the processing system are written. In the section of annexes, datasheet of the devices used in the project is described, as well as source code.